2023
DOI: 10.1093/nar/gkac1240
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of sequence divergence for repeat-mediated deletions shows a polarity that is mediated by MLH1

Abstract: Repeat-mediated deletions (RMDs) are a type of chromosomal rearrangement between two homologous sequences that causes loss of the sequence between the repeats, along with one of the repeats. Sequence divergence between repeats suppresses RMDs; the mechanisms of such suppression and of resolution of the sequence divergence remains poorly understood. We identified RMD regulators using a set of reporter assays in mouse cells that test two key parameters: repeat sequence divergence and the distances between one re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 76 publications
5
15
0
Order By: Relevance
“…In a model with a single mismatch in a 152-bp segment, SSA events exhibited a modest 60–80% bias in correcting the mismatch prompted by the shorter of the two nonhomologous tails (33 nt vs. 11 nt) and that the pattern is reversed when cleavage creates tails of 0 and 42 nt [ 41 ]. Another recent study by Trost et al [ 42 ] found that mismatches proximal to a nonhomologous tail were preferentially removed. However, unlike in budding yeast, MLH1 as well as MSH6 caused a reduction in SSA outcomes with mismatched substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a model with a single mismatch in a 152-bp segment, SSA events exhibited a modest 60–80% bias in correcting the mismatch prompted by the shorter of the two nonhomologous tails (33 nt vs. 11 nt) and that the pattern is reversed when cleavage creates tails of 0 and 42 nt [ 41 ]. Another recent study by Trost et al [ 42 ] found that mismatches proximal to a nonhomologous tail were preferentially removed. However, unlike in budding yeast, MLH1 as well as MSH6 caused a reduction in SSA outcomes with mismatched substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, Mlh1 and Pms1 are needed for mismatch correction per se but showed no effect on heteroduplex rejection in SSA. Trost et al also examined the bias in repair when one nonhomologous tail was 268 nt long and the other varied from 16 nt to 9100 nt [ 42 ]. Longer tails impaired SSA both for perfectly matched 267-bp repeats or for 1–3% divergent sequences.…”
Section: Discussionmentioning
confidence: 99%
“…MSI is a feature of many disorders, most of which are neoplastic, with Lynch syndrome being the most well-known non-neoplastic disorder. Protein dysfunction in the MMR family is involved in the occurrence of Lynch syndrome, with most families diagnosed with Lynch syndrome having MLH1 and MSH2 mutations, some families having MSH6 mutations, and a few families having PMS2 mutations ( 29 ). The occurrence of Lynch syndrome and partial sporadic colorectal cancer is not related to oncogene activation and tumor suppressor gene inactivation, rather it is caused by MSI due to mutations in mismatch repair genes ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This annealing causes the formation of 3' nonhomologous tails which are removed prior to ligation, resulting in an RMD [10]. Since RMDs are inherently mutagenic, several pathways appear to suppress these events [1,2,[10][11][12]. In particular, RMDs between divergent repeats are prone to heteroduplex rejection mechanisms via the DNA mismatch repair (MMR) pathway, and the BLM/TOP3a/ RMI1/RMI2 complex [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%